Wakhan Woluswali in Badakhshan. Observations and reflections from Afghanistan’s periphery - Felmy, Sabine; Kreutzmann, Hermann (ERDKUNDE, 2004)
The rediscovery of three worlds is taken as a conceptual point of departure for an empirical survey in a country which is described in that theory as pre-modern. Afghanistan is the spatial laboratory for a case study in which the contemporaneity of globalization and fragmentation is envisaged. Centralized power and infrastructures are analysed towards their effectiveness in the Afghan periphery. In a remote part of the Northern Alliance’s sphere of control an assessment of the livelihood conditions, exchange relations and dependency structures is attempted in combination with a comparison of certain aspects from the period prior to the 1978 Saur Revolution. Presently international development organizations are well represented although their activities seem not to affect the poor prospects for the future. Social and regional disparities seem to increase and lead to further growth of inequality.